2012
DOI: 10.1097/scs.0b013e31824e7302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lidocaine Plus Epinephrine and Prilocaine on Autologous Fat Graft Survival

Abstract: Although fat grafting is frequently used in plastic surgery practice, debate about the viability of the graft still persists owing to its questionable long-term success. The ultimate aim is to obtain long-term graft viability. Vascularization of the graft is essential for this purpose. The effects of 2 different local anesthetic preparations frequently used during harvesting of fat grafts on long-term graft survival were compared with angiogenesis and volumetric measurements. Twenty-four male Wistar rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…28,29 Furthermore, the implantation of adipose tissue pretreated with saline or lidocaine and epinephrine demonstrated no significant effect on fat graft volumes or histologic architecture. 30,31 Analysis of different anesthesia drugs demonstrated greater adipose stem cell viability within adipose tissue treated with bupivacaine, mepivacaine, ropivacaine, and lidocaine compared with combined treatment with articaine and epinephrine. 32 Although one would not expect variability between amides, epinephrine may affect the α 1 receptors on the surrounding tissues supporting the implanted cells.…”
Section: Donor-site Preparationmentioning
confidence: 99%
“…28,29 Furthermore, the implantation of adipose tissue pretreated with saline or lidocaine and epinephrine demonstrated no significant effect on fat graft volumes or histologic architecture. 30,31 Analysis of different anesthesia drugs demonstrated greater adipose stem cell viability within adipose tissue treated with bupivacaine, mepivacaine, ropivacaine, and lidocaine compared with combined treatment with articaine and epinephrine. 32 Although one would not expect variability between amides, epinephrine may affect the α 1 receptors on the surrounding tissues supporting the implanted cells.…”
Section: Donor-site Preparationmentioning
confidence: 99%
“…There are only a few experimental or clinical studies focused on this subject, and mostly some expert opinion was reported in the literature. 1,[13][14][15][16] In this article, long-term clinical and histopathologic effects of the tumescent solutions containing different combinations of lidocaine and adrenaline were investigated in a rat model.…”
Section: Discussionmentioning
confidence: 99%
“…The inguinal fat pad is a big subcutaneous fat source considering the size of the rats' body and can be harvested without causing significant damage to the rat. However, the fat pad is actually very small, and the whole fat pad weights approximately 1 g. 16 It is extremely difficult to harvest it with routine liposuction procedure, and most of the inguinal fat pad spreads over the neighboring tissues or gets stuck in the cannula. Therefore, in many studies, the inguinal fat pad was harvested surgically in en bloc fashion and trimmed into small pieces before the reimplantation process.…”
Section: Discussionmentioning
confidence: 99%
“…Time from grafting also varied widely, clearly affecting the tissue reaction seen on biopsy results. Although fat apoptosis has been shown to reach a maximum at 30 days after transfer, 27 the articles examined harvested fat over a range of 1 day to 65 months after transfer. This variable period prevents direct comparison, as the inflammatory and survival response is unequivocally time dependent.…”
Section: Discussionmentioning
confidence: 99%